A Sultan Poet in the Perception of “İnsan-ı Kâmil”: Muhibbî / İnsan-ı Kâmil Olma Yolunda Bir Sultan Şair: Muhibbî - Nazire Erbay (Folklor/Edebiyat, 2020)
For centuries the meaning of man in the world has been tried to be meaningful in all branches of art in the world literature. It is important to look at the literary text in order to investigate the self-view of man and his struggle for existence according to centuries. Classical poets have tried to understand and position themselves on the earth in the context of the mystic which is the equivalent of evolution in Sufism on an individual level. The aim of this study is to research Muhibbi, who is a sultan poet, through his poems in order to get to know personality and literary sense. For this reason, the concept of insan-ı kâmil was taken as a subject. For ordinary people, insan-ı kâmil perception is different. The difference of the perception of this concept for a sultan is revealed in the text. Here, also, reference is made to the sultan-poet who has not seen many examples in the history of world literature. Muhibbi is one of the important sultan poets of Ottoman literature. Apart from being Muhibbi, sultan or poet, the couplets he wrote as servants are quite remarkable. The poet expresses being a servant to Allah as a sultan by means of nurturing his self. In this study, couplets in which Muhibbi emphasizes the sultanate in his ghazals are highlighted. The themes of poet sultan, human, servant and perfect human are emphasized with extreme examples. In these couplets, it is important that Suleiman the Magnificent promotes being a perfect human being as a sultan.